Coproximinality in the Space of Bounded Functions - Eyad Abu-Sirhan; Zuhier Altawallbeh (International Journal of Mathematics and Mathematical Sciences)
As a counterpart to best approximation in Banach spaces, the best coapproximation was introduced by Franchetti and Furi (1972). In this paper, we shall consider the relation between coproximinality of a nonempty subset M of a Banach space X and of C(S, M) in C(S, X).